Outcomes of Sick Neonates Transported to a Tertiary Care Hospital by a Trained Team, in Northern India - Bijaylaxmi Behera; Babu Lal Meena (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: In developing countries, like ours, the major causes of neonatal mortality are Prematurity, Birth asphyxia and Sepsis. Although institutional delivery and in utero transport of newborn is the safest way to transport but it is difficult to anticipate preterm deliveries and perinatal illnesses. Moreover, transport with a well equipped and manned team improves neonatal outcomes than self transport. Hence, with the above hypothesis this study was conducted to analyse the profile of newborn babies transported to our unit by our team. Aim: To study the outcome of the sick neonates transported by a well equipped and manned neonatal transport to a Tertiary Care Hospital, indications of transport and also evaluate their condition at arrival. Materials and Methods: This was a retrospective longitudinal descriptive study, including 101 extramural neonates who were transported by a well equipped and manned team, to a Tertiary Care Hospital in Northern India. Transport details along with demographic parameters and clinical features prior to transport and at arrival were recorded. Follow-up was done for all neonates till discharge or death. Transport, clinical variables and Score for Neonatal Acute Physiology-Perinatal Extension ll (SNAPPE-II) were correlated with outcome using logistic regression analysis. Results: Total 101 newborn infants were transported. Fiftyeight babies were term and 43 were preterm. Birth asphyxia, Meconium Aspiration Syndrome, Hyaline Membrane Disease, Transient Tachypnea of Newborn, Congenital Cyanotic Heart Disease, Neonatal Jaundice, Pneumonia, Hypoglycaemia, Preterm, Fever, Feed intolerance were the major indications for transport. Total 16 neonates died. Out of all babies at admission,14.8% of babies were still hypothermic, 10.8% were still hypoxic , 4.9% were still hypoglycemic and 14.8% were still in shock. SNAPPE score >40, hypoglycaemia, hypothermia, hypoxia and shock correlated with poor outcome. Distance did not correlate with the outcome. Conclusion: Stabilising newborns prior to transport is crucial and neonatal transport is not dependent on distance. Hypothermia, hypoglycaemia, hypoxia and shock should be managed in neonates before and during transport as they affect their outcomes.